Service Constraint NCBQ trust orient secure transmission with IoT devices for improved data security in cloud using blockchain. (December 2022) - Premkumar, R.; Sathya Priya, S.
Abstract: Problem of secure transmission in cloud systems has been well studied; there exist number of approaches discussed around the problem. Number of threats has been identified in cloud which targets the services and data behind them. To mitigate the threats, different approaches are discussed in literature. The most approaches uses behavior of user in measuring trust, and some of them uses data level features in measuring trust of user. Also, various data encryption schemes are discussed which suffer with poor performance in security achievement. To handle this issue, an efficient Service Constraint NCBQ (Network Condition and Behavior Quality) Trust orient secure transmission protocol (SCNCQB-TSTP) is presented in this article. The proposed model involves in secure transmission by analyzing various factors of network, user behavior and quality of service. The method discovers set of routes to reach the service point and fetches several information about the transmission route like traffic, transmission frequency, bandwidth, IoT devices, hop count, throughput, and bandwidth utilization. According to the above information fetched about different routes, the method analyzes the trust of each route in three ways like Network Support Analysis, Behavior Support Analysis and QoS-Support Analysis. Based on the result of different analysis, the method estimates the value of Secure Transmission Score (STS). According to the value of STS, an optimal route has been selected to perform data transmission. Similarly, the method adapts Service Constraint Blockchain Model (SCBM) towards data security, which classifies the services in various levels. According to the service claimed by the user, the service data has been encrypted with specific class of scheme and key. Further, encrypted data has been placed is adapted to block chain to perform data transmission. The proposed SCNCQB-TSTP model improves the performance of secure transmission and data security.